Sodium Hydrosulfide Induces Resistance Against Penicillium expansum in Apples by Regulating Hydrogen Peroxide and Nitric Oxide Activation of Phenylpropanoid Metabolism - Deng, Huiwen; Wang, Bin; Liu, Yongxiang; Ma, Li; Zong, Yuanyuan; Prusky, Dov; Bi, Yang (Frontiers in Microbiology, 2021)
As a multifunctional signaling molecule, hydrogen sulfide (H2S) has been reported to induce plant responses to a variety of abiotic stresses. However, the possibility that H2S treatments induce resistance of apple fruit against the biotic factor, Penicillium expansum and their possible mechanism of action were not reported yet. In present study, fumigation of apple fruits during 12h using 5 mM sodium hydrosulfide (NaHS, the exogenous donor of H2S) reduced the diameter of lesions development in fruit colonized by P. expansum. NaHS treatment dramatically promoted the synthesis of endogenous H2S, hydrogen peroxide (H2O2), and nitrogen oxide (NO). In vivo treatment of NaHS enhanced the activity of phenylalanine ammonia-lyase, cinnamate 4-hydroxylase, p-coumarate:coenzyme a ligase isoenzymes, caffeoyl-CoA-O-methyltransferase, caffeic acid-O-methyltransferase, ferulic acid-5-hydroxylase, cinnamyl-CoA reductase, and cinnamyl-alcohol dehydrogenase. The treatment facilitated as well the production of specific phenolic acids such as cinnamic acid, p-coumaric acid, caffeic acid, ferulic acid, and sinapic acid, total phenolic compounds, p-coumaroyl alcohol, coniferyl alcohol, sinapyl alcohol, and lignin. This treatment induced the resistance in apple fruit through H2O2 and NO-mediated activation of phenylpropanoid metabolism.